2013
DOI: 10.1186/1478-4491-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of rural health workforce in five counties in China: research design and baseline description

Abstract: BackgroundThe village doctors have served rural residents for many decades in China, and their role in rural health system has been highly praised in the world; unfortunately, less attention has been paid to the health workforce during the ambitious healthcare reform in recent years. Therefore, we conducted a longitudinal study to explore the current situation and track the future evolution of the rural healthcare workforce.MethodsThe self-administered structured Village Clinic Questionnaire and Village Doctor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 30 publications
2
52
0
Order By: Relevance
“…13 Studies have shown that recruitment is influenced by both financial and nonfinancial incentives. 14,15 In our study, results about the unattractiveness of the job as a village doctor leading to a decreased amount of village doctors are consistent with the findings from studies in central and western China. [16][17][18] The study attempted to understand how urbanisation influences the development of village doctors in eastern China and the challenges they face (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…13 Studies have shown that recruitment is influenced by both financial and nonfinancial incentives. 14,15 In our study, results about the unattractiveness of the job as a village doctor leading to a decreased amount of village doctors are consistent with the findings from studies in central and western China. [16][17][18] The study attempted to understand how urbanisation influences the development of village doctors in eastern China and the challenges they face (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Less than 10% of the village doctors had heard that young people in their same villages wanted to become village doctors, and more than 90% of village doctors did not want their children to follow their path to become village doctors. 14 (1.7%) 40 (4.8%) 0 (0.0%) 95 (11.3%) 6 (0.8%) 75 (9.0%) 21 (2.5%) †Indicates number of responses in the category, and percentages represent portion of actual number of responses. ①, too old and no energy to do other career; ②, being a doctor as a kind of responsibility; ③, lack of new staff; ④, lack of other skills; ⑤, high income; ⑥, main economic source; ⑦, have social pension insurance; ⑧, hometown feelings; ⑨, be respected by local residents.…”
Section: Future Development For Village Doctorsmentioning
confidence: 99%
“…Existing policies apply mainly to the provision of curative services by village doctors and do not extend to preventive care [31]. We therefore designed a performance-based feedback and financial incentive payment, which serves to address this gap.…”
Section: Discussionmentioning
confidence: 99%
“…The self-administered structured Village Doctor Questionnaire, modified from the official questionnaire from the MOH after three focus groups, in-depth interviews in Hebei Province, and a pilot survey in Sichuan Province, was the tool to investigate the village doctors in this study [16]. …”
Section: Methodsmentioning
confidence: 99%
“…All of those variables were consistent with the official statistics, and had been used in the previous study [16]. …”
Section: Methodsmentioning
confidence: 99%